Influence of laser speed on the area-specific resistance in welded stainless steel for solid oxide fuel cell interconnect - Mohd Faizal, Tukimon; Hamimah, Abd Rahman; Shahrin Hisham, Amirnordin; Aiman, Mohd Halil; Khairul Anuar, Salleh; Huai, Tan Kang; Zolhafizi, Jaidi; Abdelghani Elshaikh, Mohamed Abdelghani Elsayed (Penerbit Akademia Baru, 2024)
The interconnect is one of the most important components in a solid oxide fuel cell (SOFC), as it is structurally and electrically connected to the stacked unit cells. One of the most important characteristics of an interconnect is that it must have a low area-specific resistance (ASR) to improve its electrical conductivity. In this study, welded ferritic stainless steel 430 (SS430) was fabricated by laser welding to analyse the ASR at different working temperatures. Digital microscope (DM) and electrochemical impedance (EIS) were used to study the structure of the process samples to investigate the welded area and ASR. The ASR was measured using C-V analysis via a two-point dual-probe technique at 400°C, 500°C, 600°C and 700°C. The results show that the ASR is lower in the middle part of the welded area than at the start and end areas of the welded parts. In addition, choosing the right range of laser speed played an important role in lowering the ASR. Therefore, a lower ASR is important for the SS430 to become an interconnect in SOFC.